Simulation and Implementation of Microcontroller Based Printed Circuit Board Ready Circuits for Technical Training and Demonstration - Oyebola, Blessed Olalekan; Eze Blessing, E. (Asian Journal of Engineering and Applied Technology, 2018)
The paper presents designed and constructed microcontroller based PCB ready on five automation circuits as an attempt to aid technical education on microcontroller circuits’ simulation in Computer Engineering Technology. The designs were of three stages that include circuit design and simulation by using Proteus software, printed circuit board (PCB) production using manual techniques and construction of five selected circuits (Seven Segment to Display Number 0-9, seven Segment Counter to Count 0-99, Matrix Led to Display A-Z, Digital Thermometer and Motion Sensor to Switch 10 Points of Loads) for purpose of training. The microcontroller programing were done in Mikro C programming platform. The presented hand-on circuits have proved to be instructive to trainees.